Peningkatan Pendapatan Keluarga Pertanian Berkelanjutan: Studi Kasus Pilot Project Kawasan Rumah Pangan Lestari dalam Program Lumbung Mataraman di Daerah Istimewa Yogyakarta - Riawanti, Wahyu (Optimum: Jurnal Ekonomi dan Pembangunan, 2017)
Sustainable farming became a bit more notorious after global idea of Sustainable Development Goals (SDGs) was introduced in 2015. In national Indonesian level, the idea was interpreted well in national program calledÂ  Sustainable Food Providing Households (KRPL-Ind). KRPL program was designed to enermously sustaining land in household level. Furthermore, this idea was translated in local level based on the locality and spatial character. InÂ  Yogyakarta Special District, sustainable farming for limited land was constructed in Food Security Body with Lumbung Mataraman Program. This research was aimed to reveal the entity of program. It includes what obstacle faced and that effort can suceed it. Method used in this researchwas Focus Group Discussion and intensive observation in 5 farmers group. The early research was organized in different location of 4 districts and municipal. The early result can be reported as two main aspects related to human resource and propar government program. The early conclusion were: (1) human resources and the preparedness of the farmers group (2) sustainable program for sustainable result